1996
DOI: 10.1111/j.1467-8551.1996.tb00116.x
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Service Quality and Service Characteristics on Customer Retention: Small Businesses and their Banks in the UK1

Abstract: The recent developments in relationship marketing have increasingly focused attention on the beneficial effects of customer retention. The notion of building relationships and delivering quality service in order to encourage loyalty is perhaps of particular importance in the service sector where it is often argued that customer attraction costs are significantly higher than retention costs. Central to the idea of investment in the development of service quality and customer relationships is the belief that suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
136
0
4

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 217 publications
(152 citation statements)
references
References 30 publications
5
136
0
4
Order By: Relevance
“…This fi nding is in accordance with the literature, as researchers such as Zeithaml et al , 1 Ennew and Binks, 49 Chang and Wildt, 44 Headley and Miller 48 and Boulding et al 34 also found that service quality has an infl uence on purchase intention.…”
Section: Discussionsupporting
confidence: 80%
“…This fi nding is in accordance with the literature, as researchers such as Zeithaml et al , 1 Ennew and Binks, 49 Chang and Wildt, 44 Headley and Miller 48 and Boulding et al 34 also found that service quality has an infl uence on purchase intention.…”
Section: Discussionsupporting
confidence: 80%
“…Colgate et al (1996) also noted that it is not always the case that customer defection is the inverse to loyalty, while Levesque and Mc Dougall (1993) suggested that, "even a problem is not solved, approximately half of the customers would remain with the firm". This may be due to switching costs, lack of perceived differentiation of alternatives, location constraints on choice, time or money constraints, habit or inertia which are not related to loyalty (Bitner, 1990;Ennew & Binks, 1996).…”
Section: Customer Loyaltymentioning
confidence: 99%
“…A customer may demonstrate his/her retention propensity in many ways: by expressing preference for a company over others, by continuing to buy from it or by increasing its business in the future (Zeithaml et al, 1996). Meanwhile, Enne and Binks (1996) [31] differentiated between two dimensions of retention: the continuance of a particular relationship (e.g. contract renewal) and the retention of the customer, which gives firms the opportunity to sell a variety of products and services.…”
Section: Relationship Benefitsmentioning
confidence: 99%